New understanding of the complex structure of knee menisci: Implications for injury risk and repair potential for athletes - Rattner, J. B.; Matyas, J. R.; Barclay, L.; Holowaychuk, S.; Sciore, P.; Lo, I. K. Y.; Shrive, N. G.; Frank, C. B.; Achari, Y.; Hart, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
Menisci help maintain the structural integrity of the knee. However, the poor healing potential of the meniscus following a knee injury can not only end a career in sports but lead to osteoarthritis later in life. Complete understanding of meniscal structure is essential for evaluating its risk for injury and subsequent successful repair. This study used novel approaches to elucidate meniscal architecture. The radial and circumferential collagen fibrils in the meniscus were investigated using novel tissue-preparative techniques for light and electron microscopic studies. The results demonstrate a unique architecture based on differences in the packaging of the fundamental collagen fibrils. For radial arrays, the collagen fibrils are arranged in parallel into ~10 µm bundles, which associate laterally to form flat sheets of varying dimensions that bifurcate and come together to form a honeycomb network within the body of the meniscus. In contrast, the circumferential arrays display a complex network of collagen fibrils arranged into ~5 µm bundles. Interestingly, both types of architectural organization of collagen fibrils in meniscus are conserved across mammalian species and are age and sex independent. These findings imply that disruptions in meniscal architecture following an injury contribute to poor prognosis for functional repair.